Antimicrobial activity of rhodomyrtone isolated from Rhodomyrtus tomentosa (Aiton) Hassk. Issue 17 (1st September 2020) - Bach, Quynh N.; Hongthong, Sakchai; Quach, Lien T.; Pham, Lieu V.; Pham, Thuc V.; Kuhakarn, Chutima; Reutrakul, Vichai; Nguyen, Phuong T.M.
Abstract: Rhodomyrtone was isolated from the leaves of Rhodomyrtus tomentosa (Aiton) Hassk grown in Vietnam using chromatographic methods. Its chemical structure was confirmed by means of spectroscopic data analysis. The pH drop measurement, enzyme activity assays and fluorescence stain were used to examine rhodomyrtone anticaries activity. It was found that rhodomyrtone suppressed acid production by Streptococcus mutans, a major cariogenic agent in human by inhibiting enzyme activities responsible for acid production and tolerance, including membrane bound enzymes F-ATPase and phosphotransferase system (PTS), as well as glycolysis enzymes glyceraldehyphosphate dehydrogenase (GAPDH) and pyruvate kinase (PK) in cytoplasm with the IC50 values of 24 μM, 19 μM, 23 μM and 28 μM, respectively. Moreover, 50 μM rhodomyrtone reduced biofilm biomass formed by S. mutans up to 59% ( p  < 0.05). Fluorescent images indicated that cells on the biofilms were significantly killed. Thus, rhodomyrtone is a new and potential anticaries agent against S. mutans . Graphical Abstract: